Answer:
Step-by-step explanation:
Given that
-3a+6b=a+4b
We want to make b subject of formula
First to remove the 4b in the Right hand side of the equation
Subtract 4b from both side of the equation
-3a+6b-4b=a+4b-4b
Then we have,
-3a+2b=a
Now to remove the -3a from the left hand side of the equation add 3a to both side
Then,
-3a+2b+3a=a+3a
2b-3a+3a=4a
Then, 2b=4a
Divide both side by 2
2b/2=4a/2
b=2a.
F(x) = 5(x + 4) – 80
f(x) = 5(x + 8) – 80
f(x) = 5(x + 4)2 – 80
f(x) = 5(x + 8)2 – 80
Answer:
30
Step-by-step explanation:
x + 23 = ?
x = 7
All we need to do is plug in x =7 to the first equation:
7 + 23 = ?
We simplify and get:
30 = ?
Answer:
it's 8
Step-by-step explanation:
(10×1/5)^3=2^3=8
Answer:
Step-by-step explanation:
The common difference (d) can be found using the first and 4th terms:
a1 = 3
a4 = a1 +d(4 -1)
-9 = 3 +3d . . . . . simplify
-3 = 1 + d . . . . . . divide by 3
-4 = d . . . . . . . . . subtract 1
Then ...
x = a1 + d = 3 -4 = -1
y = x + d = -1 -4 = -5
The values of x and y are -1 and -5, respectively.